Pyroptosis of resident macrophages differentially orchestrates inflammatory responses to Staphylococcus aureus in resistant and susceptible mice. Issue 3 (21st January 2015) - Accarias, Solène; Lugo‐Villarino, Geanncarlo; Foucras, Gilles; Neyrolles, Olivier; Boullier, Séverine; Tabouret, Guillaume
<x xml:space="preserve">Abstract</x> The relationship between Staphylococcus aureus and innate immunity is highly complex and requires further investigation to be deciphered. i.p. challenge of C57BL/6 and DBA/2 mice, resistant and susceptible to the infection, respectively, resulted in different patterns of cytokine production and neutrophil recruitment. Staphylococcus aureus infection induced macrophage pyroptosis, an inflammasome‐dependent cell death program, whose rates significantly differed between C57BL/6 and DBA/2 mice. Fast rate pyroptosis of C57BL/6 macrophages released high levels of IL‐1β but limited the synthesis of other cytokines such as TNF‐α, IL‐6, CXCL1, and CXCL2. Conversely, the extended survival of DBA/2 macrophages allowed substantial production of these NF‐κB‐related cytokines. Phenotyping of resting macrophages in different mouse strains revealed differential predisposition toward specific macrophage phenotypes that modulate S. aureus‐mediated inflammasome activation. Treatment of DBA/2 susceptible mice with inflammasome inducers (i.e. nigericin and ATP) artificially increased pyroptosis and lowered the levels of NF‐κB‐related inflammatory cytokines, but restored IL‐1β to levels similar to those in C57BL/6 mice. Collectively, this study promotes the concept that, in association with host genetics, the basal phenotype of resident macrophages influences the early inflammatory response and possibly participates in S. aureus infection outcome via the inflammasome pathway and subsequent pyroptosis.